"Summer sowing": A successful innovation to increase the adoption of key species of annual forage legumes for agriculture in Mediterranean and temperate environments. (25th March 2021) - Nutt, Brad J.; Loi, Angelo; Hackney, Belinda; Yates, Ron J.; D'Antuono, Mario; Harrison, Robert J.; Howieson, John G.
Abstract: This paper reports on the evaluation of "summer sowing, " an innovative approach to increase the adoption of recently domesticated species of hard seeded annual legumes in Mediterranean and temperate Agriculture. The research revealed that several species of annual legumes whose seed can be readily harvested on‐farm and which possess natural hard seed dormancy, may be sown into dry soil in late summer without additional processing. These studies proved that the hard seed dormancy was broken down sufficiently in the soil over 4–6 weeks to produce robust legume pastures with more than 150 seedlings per m 2 following the first winter rains, in replicated field sites established across wide agro‐ecological zones in Western Australia (WA) and New South Wales (NSW). Ornithopus sativus Brot., O. compressus L. and Trifolium spumosum L. were suitable for summer sowing based on both hard seed breakdown patterns and subsequent seedling survival in WA. While in NSW, in addition to these legumes, Biserrula pelecinus L., T. vesiculosum Savi. and T. glanduliferum Boiss. were also suitable for summer sowing. A 1.5‐ to 10‐fold increase in herbage production was achieved relative to conventionally sown T. subterraneum L. This development represents a step change in forage legume development for renovated pastures in these environments. Importantly, the experiments revealed differences in G x E effects on seedling establishment, total herbage production and seed yield in different climatic zones. The summer sowing approach is presented as a revolutionary method for pasture renovation that overcomes significant barriers to adoption.